IMPLEMENTASI PROGRAM WOMEN AND GIRLS SAFE SPACES (WGSS) DALAM MENANGANI KEKERASAN BERBASIS GENDER TERHADAP PENGUNGSI PEREMPUAN SURIAH DI PERBATASAN TURKI-SURIAH - Sinta Julianti; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The Syrian conflict since 2011 has displaced 2.5 million people to Turkey, with women being the most vulnerable group to gender-based violence, such as economic exploitation, early marriage, sexual violence, and domestic violence. This vulnerability is influenced by refugee conditions, unequal power relations, and patriarchal norms. In response, the United Nations Population Fund developed the Women and Girls Safe Spaces (WGSS) program as an effort to protect and empower refugee women, particularly in Turkey-Syria border areas such as Şanlıurfa and Hatay. This research uses a qualitative approach with descriptive qualitative methods through secondary data from official reports and related documents. The analysis focuses on the implementation of WGSS in addressing four forms of gender-based violence, as well as the achievements and challenges of its implementation in border areas. The results show that the implementation of the WGSS program not only focuses on victim care but also includes prevention and empowerment efforts through counseling services, group activities, case management, and a referral system to health services. This program contributes to increasing women's access to protection services, strengthening social support, and increasing women's courage to report experiences of violence. The program's achievements are also evident in the increasing number of service recipients and the expansion of its reach, although available data is largely national. Furthermore, the implementation of the WGSS reflects the implementation of women's protection norms as stipulated in CEDAW, particularly in addressing gender-based violence and fulfilling the rights of women in vulnerable situations. The integration of the WGSS into the Turkish government's service system in 2019 and its continued service in 2020 demonstrates that the program has contributed to and played a role in strengthening a more sustainable protection system for Syrian refugee women. Keywords: CEDAW, Gender-Based Violence, Syrian Refugee Women, Turkey, WGSS.